PD-1 /PD-L1 checkpoint in hematological malignancies. (April 2018) - Annibali, O.; Crescenzi, A.; Tomarchio, V.; Pagano, A.; Bianchi, A.; Grifoni, A.; Avvisati, G.
Highlights: PD-1/PD-L1 axis and its role in immune surveillance in hematological malignances. Targeting the PD-1/PD-L1 pathway to activate anti-tumor immunity. Safety, activity, and efficacy of anti–PD-1 antibody in hematological diseases. Anti-PD-1 antibody therapy enhances eradication of refractory Hodgkin Lymphoma. Anti-PD-1 and hypomethylating agents a new combination for leukemia patients. Abstract: Programmed cell death protein 1 (PD-1), is a cell surface receptor with an important role in down-regulating the immune system and promoting self-tolerance by suppressing T cell inflammatory activity. PD-1/PDL1 axis represents a checkpoint to control immune responses and it is often used as a mechanism of immune escaping by cancers and infectious diseases. Many data demonstrate its important role in solid tumors and report emerging evidences in lymphoproliferative disorders. In this review, we summarized the available data on the role of PD-1/PD-L1 checkpoint in lymphoproliferative diseases and the therapeutics use of monoclonal blocking antibodies.